2 - Emergence: The Indelible Face of Artistic Creativity in the Struggle for Self-Determination in Africa - Mlama, Penina (Africa Development, 2017)
Emergence has characterized artistic creativity throughout history due to art’s proven efficacy as a vehicle for expression and self-determination. This article critically examines emergence in artistic creativity in Africa. The discussion starts with emergence and artistic creativity under feudal systems where despite the attempt to domesticate art by kings through hiring court artists, the common citizenry vented their anger or dissatisfaction against the social injustices meted out to them by the feudal systems. This is followed by a critical discussion of the use of emergence in artistic creativity to respond to slavery and colonialism, as well as the brutal systems that shook the socio-economic foundations of African societies following independence. Emergence in artistic creativity prevailed beyond colonialism as Africans became victims of exploitation by the nationalist leaders who took over leadership in post-independent Africa. A key question addressed is whether Africa’s bondage to capitalism signals the end of emergence in artistic creativity, the age long indelible face of self-determination.